Essentials of thematic analysis - Terry, Gareth; Hayfield, Nikki (American Psychological Association, 2021)
"The brief, practical texts in the Essentials of Qualitative Methods series introduce social science and psychology researchers to key approaches to capturing phenomena not easily measured quantitatively, offering exciting, nimble opportunities to gather in-depth qualitative data. In this book, Gareth Terry and Nikki Hayfield introduce readers to reflexive thematic analysis, a method of analyzing interview and focus group transcripts, qualitative survey responses, and other qualitative data. Central to this method is the recognition that we are all situated in a context and see and speak from that position. This leads researchers to produce knowledge that represents situated truths which bring insight into other people's perspectives on a given topic. About the Essentials of Qualitative Methods book series: Even for experienced researchers, selecting and correctly applying the right method can be challenging. In this groundbreaking series, leading experts in qualitative methods provide clear, crisp, and comprehensive descriptions of their approach, including its methodological integrity, and its benefits and limitations. Each book includes numerous examples to enable readers to quickly and thoroughly grasp how to leverage these valuable methods"- Resumé vydavatel
Keywords: kvalitativní výzkum -- metodologie; společenské vědy; sociální výzkum -- metodologie; qualitative research -- methodology; social sciences; social research -- methodology; příručky; handbooks and manuals